The Relationship Between Wood 1820 Restaurant Atmosphere And Service Quality On Guest Satisfaction At High Season Yuan Garden Hotel - Aditya Ceni Rahmadian; Ramang Husin Demolingo (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
The purpose of this study was to examine how restaurant ambiance and service quality influence customer satisfaction at Wood 1820 Restaurant, Yuan Garden Hotel, Pasar Baru, during peak season. The increasing number of customers during the busiest time of the year, which makes the restaurant busier and can impact customer experience, was the driving force behind this study. One hundred respondents who came during the peak season were given a questionnaire as part of the quantitative research process. IBM SPSS version 29 was to evaluate the data using multiple linear regression, validity, reliability, classical assumptions, t-test, F-test, and coefficient of determination. The results showed that customer satisfaction was positively and significantly influenced by restaurant decor and service quality. Compared to restaurant ambiance, service quality was the factor with the greatest impact. According to the coefficient of determination value, 47.8% of customer satisfaction can be explained by these two variables, with the remainder influenced by variables not included in this study. These results suggest that to maintain customer satisfaction during peak season, service management and restaurant ambiance must be considered.